Chromium group metal doped platinum alloy catalyst as well as preparation method and application thereof
By doping chromium group metal elements into the PtM alloy catalyst to form an X-PtM/C alloy catalyst, the problem of insufficient activity and durability of the existing PtM alloy catalyst is solved, and the performance of the catalyst is significantly improved. It is suitable for oxygen in fuel cells Reduction reaction.
Patent Information
- Application Number
- CN202411648876.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-19
AI Technical Summary
The existing alloy catalyst formed by Pt and transition metal M (Fe, Co or Ni) lacks catalytic activity and durability under the operating conditions of the fuel cell, especially the dissolution and structural degradation of the transition metal lead to a degradation of performance.
The PtM alloy catalyst with chromium group metal doped is formed through secondary reduction and high-temperature heat treatment, where X is Cr, Mo or W, M is Fe, Co or Ni, and the chromium group element is doped It plays an electron buffering role in PtM alloys to improve the activity and stability of the catalyst.
The Pt activity and durability of the catalyst were significantly improved. The mass activity (MA) of Cr-PtNi/C was about 8.1 times that of Pt/C, and the mass activity (MA) of Mo-PtNi/C was about 5.0 times that of Pt/C. , the mass activity (MA) of Cr-PtCo/C is about 6.1 times that of Pt/C and shows higher stability in the aging test.
Smart Images

Figure CN119447343A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a platinum alloy catalyst and a preparation method and application thereof, and belongs to the field of new energy materials. Background Art
[0002] At present, the performance, cost and mass production of proton exchange membrane fuel cells (PEMFC) need to be improved. Commercial Pt / C catalysts can effectively accelerate the electrochemical reaction rate, but the operating environment of fuel cells is harsh. Pt / C catalysts are prone to degradation under high potential and strong acidic conditions, resulting in reduced performance and stability of the catalyst after cycling. Therefore, reducing costs while preparing highly active and durable electrocatalysts is the key to solving the above problems. Studies have shown that the formation of alloy catalysts by Pt and transition metal M (such as transition elements Fe, Co, Ni, etc. in the fourth period) can not only reduce the amount of precious metal Pt, but also change the binding strength of Pt and oxygen intermediates by adjusting the electronic structure and geometric structure, thereby achieving enhanced ORR activity and stability. Among all PtM catalysts, PtNi and PtCo alloy catalysts have attracted much attention due to their excellent performance. However, since transition metals such as Ni are more easily dissolved under the operating conditions of PEMFC, the leaching of non-Pt elements leads to significant structural degradation, and the weakened strain effect leads to reduced catalytic activity and durability of the catalyst. Summary of the invention
[0003] The present invention aims to solve the technical problem that the catalytic activity and durability of the alloy catalyst formed by the existing Pt and transition metal M (Fe, Co or Ni) are insufficient, and to provide a chromium group metal doped platinum alloy catalyst and its preparation method and application. The present invention uses PtC as a precursor, performs secondary reduction and high temperature heat treatment to obtain an X-PtM / C alloy catalyst (X is Cr, Mo or W, M is Fe, Co or Ni), and the obtained catalyst Pt activity and durability are significantly improved.
[0004] The chromium group metal doped platinum alloy catalyst of the present invention is a PtM alloy nanoparticle doped with a chromium group element X uniformly supported on a carbon carrier; in the PtM alloy doped with the chromium group element X, X exists in a simple substance form, and the mass percentage of the chromium group element X is 5% to 10%; it is recorded as X-PtM / C, wherein X is Cr, Mo or W; and M is Fe, Co or Ni.
[0005] The preparation method of the chromium group metal-doped platinum alloy catalyst is carried out according to the following steps:
[0006] 1. Preparation of Pt / C by polyol reduction method: adding a carbon carrier to a mixed solution of ethylene glycol and isopropanol, and uniformly dispersing the carbon powder by ultrasonic and magnetic stirring to obtain a carbon dispersion; then adding an ethylene glycol solution of chloroplatinic acid to the carbon dispersion and stirring evenly to obtain a slurry; then adjusting the pH of the slurry to be alkaline; reducing Pt to Pt nanoparticles by microwave heating under the protection of an inert gas; then adjusting the pH of the slurry to be acidic so that the Pt nanoparticles are loaded on the carbon carrier; filtering and washing the slurry, vacuum drying it, and grinding it evenly to obtain Pt / C particles;
[0007] 2. Sodium borohydride reduction: Pt / C particles are dissolved in ultrapure water, and the Pt / C particles are evenly dispersed by ultrasonic and magnetic stirring, and a metal salt solution of a chromium group element X and a metal salt solution of M are added, and stirred evenly to obtain a mixed solution; sodium borohydride aqueous solution is added dropwise to the mixed solution under ice-water bath conditions, and stirring is continued for 2 to 3 hours after the addition is completed; then suction filtration, washing, vacuum drying, and grinding to obtain XM-Pt / C powder;
[0008] 3. High temperature annealing: placing the XM-Pt / C powder in a high temperature furnace, heating it to 700-1100°C in a reducing atmosphere or an inert atmosphere and maintaining it for 0.5-4 hours for annealing, and grinding it evenly after cooling to obtain a primary product; during the high temperature annealing process, PtM alloy nanoparticles doped with chromium group element X are formed, and the particles are supported on the carbon carrier;
[0009] 4. Acid washing treatment of heteroatoms on the catalyst surface: The initial product of step 1 is acid washed in a dilute sulfuric acid solution, then filtered and washed with ultrapure water until neutral, and vacuum dried to obtain a chromium group metal-doped platinum alloy catalyst, which is denoted as X-PtM / C.
[0010] Furthermore, the carbon carrier described in step 1 is ECP-600JD, ECP-300JD or XC-72.
[0011] Furthermore, the volume ratio of ethylene glycol to isopropanol in the mixed solution of ethylene glycol and isopropanol described in step 1 is (2-3):1.
[0012] Furthermore, in step 1, adjusting the pH of the slurry to be alkaline is to adjust the pH value to 9-13; adjusting the pH of the slurry to be acidic is to adjust the pH value to 0.5-4.
[0013] Furthermore, the concentration of chloroplatinic acid in the ethylene glycol solution of chloroplatinic acid in step 1 is 0.03M to 0.05M;
[0014] Furthermore, the ratio of chloroplatinic acid to carbon carrier in step 1 is (0.2-0.6):1.
[0015] Furthermore, the metal salt of the chromium group element X in step 2 is chromium chloride, chromium nitrate, molybdenum chloride, molybdenum nitrate, tungsten chloride or tungsten nitrate.
[0016] Furthermore, the metal salt of M in step 2 is nickel chloride, nickel nitrate, cobalt chloride, cobalt nitrate, ferric chloride or ferric nitrate.
[0017] Furthermore, the ratio of the metal salt of the chromium group element X, the metal salt of M and the metal in the Pt / C particles described in step 2 is (0.1-0.3):(0.5-1):1.
[0018] Furthermore, the concentration of the sodium borohydride aqueous solution in step 2 is 0.05-0.1M.
[0019] Furthermore, the concentration of the dilute sulfuric acid solution described in step 4 is 0.05-0.1 M, and the pickling time is 2-6 hours.
[0020] Furthermore, the inert atmosphere in steps 1 and 4 is Ar or N 2;
[0021] Furthermore, the reducing atmosphere in step 4 is a H2 / Ar mixed gas, wherein H2 accounts for 5% to 10% of the volume of the mixed gas.
[0022] The application of the chromium group metal doped platinum alloy catalyst is to use the catalyst in the cathode oxygen reduction reaction (ORR) of a fuel cell.
[0023] The beneficial effects of the present invention compared to the prior art are:
[0024] (1) The present invention can load Pt nanoparticles and transition metal M onto a carbon carrier in steps by a chemical reduction method to obtain XM-Pt / C, and form an X-PtM alloy with Pt nanoparticles in the XM-Pt / C by high-temperature annealing to obtain an X-PtM / C alloy catalyst. The X-PtM structure can effectively regulate the adsorption capacity of Pt nanoparticles for reaction intermediates, thereby improving the catalyst activity.
[0025] (2) The present invention first reduces Pt nanoparticles to prepare Pt / C as a precursor, providing deposition sites for transition metals M and X to form a stable X-PtM / C, which is beneficial to the uniform dispersion of Pt or PtM nanoparticles on the carrier surface.
[0026] (3) The PtM alloy catalyst doped with the chromium group element X of the present invention has an electron buffering effect on the alloy particles. Specifically, these elements have weak electron affinity and strong ionization tendency, and can act as electron acceptors or donors, thereby promoting the transmission of electrons in the metal alloy. This effect helps to evenly distribute the electron density, reduce local charge imbalance and polarization, and effectively improve the activity and stability of the alloy catalyst. Compared with the existing commercial platinum carbon catalyst, its catalytic activity and stability are greatly improved, among which the mass activity (MA) of Cr-PtNi / C is 0.419mA / μg Pt , about 8.1 times that of Pt / C and about 3.9 times that of PtNi / C. The mass activity (MA) of Mo-PtNi / C is 0.254A / mg Pt , which is about 5.0 times that of Pt / C. The mass activity (MA) of Cr-PtCo / C is 0.314A / mg Pt , about 6.1 times that of Pt / C and about 1.2 times that of PtCo / C. The potential of Cr-PtNi / C has no decay after aging for 30,000 cycles, and its stability is better than that of PtNi / C and Pt / C, so it can be used in the field of fuel cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a preparation flow chart of the present invention;
[0028] Figure 2 1 is an XRD diagram of Cr-PtNi / C prepared in Example 1, Pt / C prepared in Comparative Example 1, and PtNi / C prepared in Comparative Example 2;
[0029] Figure 3 is a TEM image of Cr-PtNi / C prepared in Example 1;
[0030] Figure 4 is a TEM image of Cr-PtNi / C prepared in Example 1;
[0031] Figure 5 : are ORR polarization diagrams of Cr-PtNi / C prepared in Example 1, Pt / C in Comparative Example 1, PtNi / C prepared in Comparative Example 2, and Mo-PtNi / C prepared in Example 3;
[0032] Figure 6 is a mass specific activity diagram of Cr-PtNi / C prepared in Example 1, Pt / C in Comparative Example 1, PtNi / C prepared in Comparative Example 2, and Mo-PtNi / C prepared in Example 3;
[0033] Figure 7ORR polarization diagrams of Cr-PtNi / C prepared in Example 1, Pt / C prepared in Comparative Example 1, and PtNi / C prepared in Comparative Example 2 before and after aging;
[0034] Figure 8 ORR polarization diagram of Cr-PtNi / C prepared in Example 1, Pt / C prepared in Comparative Example 1, and PtNi / C prepared in Comparative Example 2 under hydrogen and oxygen conditions in MEA;
[0035] Fig. 9 ORR polarization diagrams of Cr-PtNi / C prepared in Example 1, Pt / C prepared in Comparative Example 1, and PtNi / C prepared in Comparative Example 2 under hydrogen-air conditions in MEA;
[0036] Fig.10 2 are ORR polarization diagrams of Cr-PtCo / C prepared in Example 2, Pt / C prepared in Comparative Example 1, and PtCo / C prepared in Comparative Example 3;
[0037] Fig.11 It is a mass ratio activity diagram of Cr-PtCo / C prepared in Example 2, Pt / C in Comparative Example 1, and PtCo / C prepared in Comparative Example 3. DETAILED DESCRIPTION
[0038] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention that does not depart from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.
[0039] Example 1: The preparation method of the chromium group metal doped platinum alloy catalyst Cr-PtNi / C of this example is carried out according to the following steps:
[0040] 1. Preparation of Pt / C by polyol reduction method: weigh 48 mg ECP-600JD carbon powder was placed in a beaker, and 40 ml of a mixed solution of ethylene glycol and isopropanol was added; wherein the volume ratio of ethylene glycol to isopropanol in the mixed solution of ethylene glycol and isopropanol was 5:2; ultrasonic stirring was performed for 120 min to obtain a carbon dispersion; 0.800 ml of a 0.0385 mol / L chloroplatinic acid ethylene glycol solution was added to the carbon dispersion, and ultrasonic stirring was continued for 30 min to fully mix the mixture to obtain a slurry; then, the pH of the slurry was adjusted to 12 using a 1 mol / L NaOH ethylene glycol solution, and nitrogen was introduced into the slurry to remove the dissolved air in the solution to protect the solution; then, the slurry was placed in a microwave oven and heated for 100 s; after cooling, the pH of the slurry was adjusted to 2 using a nitric acid ethylene glycol solution, and stirring was continued for 12 hours; then, the slurry was filtered and washed 3 times, the filter residue was taken out, and vacuum dried in a vacuum drying oven at a temperature of 80°C for 8 hours; and the slurry was evenly ground to obtain Pt / C particles;
[0041] 2. Preparation of CrNi-Pt / C by sodium borohydride reduction: 40 mg of Pt / C was dissolved in ultrapure water, and the carbon powder was evenly dispersed by ultrasonic and magnetic stirring, and then 4 ml of 10 mmol / L nickel nitrate solution and 2.5 ml of 5 mmol / L chromium nitrate solution were added and stirred evenly to obtain a mixed solution; then 10 ml of 0.025 mol / L sodium borohydride aqueous solution was added dropwise to the mixed solution under ice-water bath conditions, and after the addition was completed, stirring was continued for 2 hours, and the slurry was filtered and washed 3 times, and the filter residue was taken out and placed in a vacuum drying oven at a temperature of 80°C for vacuum drying for 8 hours; it was ground evenly to obtain CrNi-Pt / C powder;
[0042] 3. High temperature annealing: CrNi-Pt / C powder is placed in a corundum magnetic boat, and then the corundum magnetic boat is placed in a tube furnace, and the temperature is raised to 900°C at 5°C / min in a H2 / Ar atmosphere and maintained for 120 minutes for annealing, and then naturally cooled to room temperature, and ground evenly to obtain a primary product; during the high temperature annealing process, Cr-doped PtNi alloy nanoparticles are formed, and the particles are supported on the carbon carrier;
[0043] 4. Acid washing for treating heteroatoms on the catalyst surface: The initial product of the step is placed in a dilute sulfuric acid solution with a concentration of 0.05 mol / L and pickled at 80°C for 120 min, then filtered and washed with ultrapure water until neutral, and the filtered residue is placed in a vacuum drying oven at 80°C for vacuum drying for 8 h to obtain a chromium group metal doped platinum alloy catalyst, recorded as Cr-PtNi / C.
[0044] Comparative Example 1: In this comparative example, a catalyst PtNi / C not doped with chromium group metal elements is prepared. The difference between this comparative example and Example 1 is that the chromium nitrate solution in step 2 is omitted, and the other steps and parameters are the same as those in Example 1. The obtained catalyst not doped with chromium group metal elements is recorded as PtNi / C.
[0045] Example 2: The preparation method of the chromium group metal doped platinum alloy catalyst Mo-PtNi / C of this example is carried out according to the following steps:
[0046] 1. Preparation of Pt / C: This step is the same as step 1 of Example 1, and Pt / C particles are obtained;
[0047] 2. Preparation of MoNi-Pt / C: 40 mg Pt / C was dissolved in ultrapure water, and the carbon powder was evenly dispersed by ultrasonic and magnetic stirring, and then 4 ml 10 mmol / L nickel nitrate solution and 2.5 ml 5 mmol / L molybdenum nitrate were added and stirred to make the slurry uniform, and then 10 ml 0.025 mol / L sodium borohydride aqueous solution was added dropwise under ice water bath conditions, and after stirring for 2 hours, the slurry was filtered, washed and vacuum dried to obtain MoNi-Pt / C catalyst, which was ground evenly for use;
[0048] 2. Take 40 mg of Pt / C and dissolve it in ultrapure water. Disperse the carbon powder evenly by ultrasonic and magnetic stirring. Then add 4 ml of 10 mmol / L nickel nitrate solution and 2.5 ml of 5 mmol / L molybdenum nitrate solution, and stir evenly to obtain a mixed solution. Then, add 10 ml of 0.025 mol / L sodium borohydride aqueous solution to the mixed solution under ice-water bath conditions. After the addition is completed, continue stirring for 2 hours, filter and wash the slurry 3 times, take out the filter residue, and place it in a vacuum drying oven at a temperature of 80°C for vacuum drying for 8 hours; grind evenly to obtain MoNi-Pt / C powder.
[0049] 3. High temperature annealing: MoNi-Pt / C powder is placed in a corundum magnetic boat, and then the corundum magnetic boat is placed in a tube furnace, and the temperature is raised to 900°C at 5°C / min in a H2 / Ar atmosphere and maintained for 120 minutes for annealing, and then naturally cooled to room temperature, and ground evenly to obtain a primary product; during the high temperature annealing process, Mo-doped PtNi alloy nanoparticles are formed, and the particles are supported on the carbon carrier;
[0050] 4. Acid washing for heteroatoms on the catalyst surface: The initial product of the step is placed in a 0.05 mol / L dilute sulfuric acid solution at 80°C for acid washing for 120 min, then filtered and washed with ultrapure water until neutral, and the filtered residue is placed in a vacuum drying oven at 80°C for vacuum drying for 8 h to obtain a chromium group metal doped platinum alloy catalyst, recorded as Mo-PtNi / C.
[0051] The XRD spectra of the Pt / C particles prepared in step 1 of Example 1, the Cr-PtNi / C catalyst prepared in step 4, and the PtNi / C catalyst prepared in comparative example 1 are as follows: Figure 2 As shown, from Figure 2 It can be seen that the doping of metal Cr and Ni causes the Pt lattice to compress, resulting in a significant rightward shift of the characteristic peak, indicating that the catalyst is an alloy particle.
[0052] Example 1 The TEM images of the Cr-PtNi / C catalyst prepared in step 4 are as follows: Figure 3 and Figure 4 shown; from Figure 3 It can be seen that the alloy catalyst obtained by step-by-step reduction is evenly distributed on the carbon support; Figure 4 It can be seen that the lattice spacing of the catalyst particles is smaller than that of pure Pt, which further indicates that the metal atoms form an alloy.
[0053] Figure 5 The ORR polarization diagrams of the Pt / C particles prepared in step 1 of Example 1, the Cr-PtNi / C catalyst prepared in step 4, the PtNi / C prepared in comparative example 1, and the Mo-PtNi / C prepared in example 2 are as follows: Figure 6 As shown, the ORR polarization diagram was measured by step voltammetry (LSV) in an oxygen-saturated 0.1 M HClO4 electrolyte with a potential range of 0.05-1.2 V and a rotation speed of 1600 rpm. Figure 6 shown; from Figure 5 and Figure 6 It can be seen that the mass activity (MA) of Pt / C is 0.0516 mA / μg Pt The mass activity (MA) of Cr-PtNi / C prepared in Example 1 is 0.419 mA / μg Pt , which is about 8.1 times that of Pt / C and about 3.9 times that of PtNi / C prepared in Comparative Example 1. The mass activity (MA) of Mo-PtNi / C prepared in Example 2 is 0.254 A / mg Pt , which is about 5.0 times that of Pt / C and about 2.4 times that of PtNi / C prepared in Comparative Example 1.
[0054] Figure 7 The ORR polarization diagrams of the Pt / C particles prepared in step 1 of Example 1, the Cr-PtNi / C catalyst prepared in step 4, and the PtNi / C prepared in comparative Example 1 before and after aging for 30,000 cycles; the aging test was conducted by conducting potential cycling in an oxygen-saturated 0.1M HClO4 electrolyte to study the stability of the catalyst, with a scan rate of 1 and a scan range of 0.6 to 1.0 V. Figure 7It can be seen that the potential of Cr-PtNi / C prepared in Example 1 has no decay after aging for 30,000 cycles, the potential of PtNi / C decays by 10 mV after aging for 30,000 cycles, and the potential of Pt / C decays by 18 mV after aging for 30,000 cycles. It can be seen from the comparison that the stability of Cr-PtNi / C is much better than that of Pt / C.
[0055] The ORR polarization tests of the Pt / C particles prepared in step 1 of Example 1, the Cr-PtNi / C catalyst prepared in step 4, and the PtNi / C prepared in comparative example 1 under different atmospheres in MEA are as follows: Figure 8 and Fig. 9 As shown, Figure 8 The catalyst was measured in the 850e fuel cell test system at a temperature of 80°C, a relative humidity of 100%, hydrogen and oxygen were introduced into the anode and cathode respectively, and the back pressure was 100kPa. Fig. 9 The catalyst was tested in an 850e fuel cell test system at a temperature of 80°C, a relative humidity of 100%, hydrogen-air flowed into the anode and cathode respectively, and a back pressure of 200 kPa. The maximum power density of the Cr-PtNi / C catalyst prepared in Example 1 under a hydrogen-oxygen atmosphere reached 2.9 W / cm 2 , which is about 1.6 times that of Pt / C and about 1.2 times that of PtNi / C prepared in Comparative Example 1. The maximum power density of the Cr-PtNi / C catalyst prepared in Example 1 under hydrogen-air atmosphere reaches 1.9 W / cm 2 , which is about 1.2 times that of Pt / C and about 1.1 times that of PtNi / C prepared in Comparative Example 1.
[0056] Example 3: The preparation method of the chromium group metal doped platinum alloy catalyst Cr-PtCo / C of this example is carried out according to the following steps:
[0057] 1. Preparation of Pt / C: This step is the same as step 1 of Example 1; Pt / C particles are obtained;
[0058] 2. Preparation of CrCo-Pt / C by sodium borohydride reduction: 40 mg of Pt / C was dissolved in ultrapure water, and the carbon powder was evenly dispersed by ultrasonic and magnetic stirring, and then 4 ml of 10 mmol / L cobalt nitrate solution and 2.5 ml of 5 mmol / L chromium nitrate solution were added and stirred evenly to obtain a mixed solution; then 10 ml of 0.025 mol / L sodium borohydride aqueous solution was added dropwise to the mixed solution under ice-water bath conditions, and after the addition was completed, stirring was continued for 2 hours, and the slurry was filtered and washed 3 times, and the filter residue was taken out and placed in a vacuum drying oven at a temperature of 80°C for vacuum drying for 8 hours; it was ground evenly to obtain CrCo-Pt / C powder;
[0059] 3. High temperature annealing: CrCo-Pt / C powder is placed in a corundum magnetic boat, and then the corundum magnetic boat is placed in a tube furnace, and the temperature is raised to 900°C at 5°C / min in a H2 / Ar atmosphere and maintained for 120 minutes for annealing, and then naturally cooled to room temperature, and ground evenly to obtain a primary product; during the high temperature annealing process, Cr-doped PtCo alloy nanoparticles are formed, and the particles are supported on the carbon carrier;
[0060] 4. Acid washing for treating heteroatoms on the catalyst surface: The initial product of the step is placed in a dilute sulfuric acid solution with a concentration of 0.05 mol / L and pickled at 80°C for 120 min, then filtered and washed with ultrapure water until neutral, and the filtered residue is placed in a vacuum drying oven at 80°C for vacuum drying for 8 h to obtain a chromium group metal doped platinum alloy catalyst, recorded as Cr-PtCo / C.
[0061] Comparative Example 2: In this comparative example, a catalyst PtCo / C not doped with chromium group metal elements is prepared. The difference between this comparative example and Example 3 is that the chromium nitrate solution in step 2 is omitted, and the other steps and parameters are the same as those in Example 3. The obtained catalyst not doped with chromium group metal elements is recorded as PtCo / C.
[0062] The ORR polarization test and mass activity of the Pt / C prepared by step 1, the Cr-PtCo / C catalyst prepared by step 4 and the PtCo / C catalyst prepared by comparative example 2 are as follows: Fig.10 and Fig.11 As shown, from Fig.10 and 11 It can be seen that the mass activity (MA) of Cr-PtCo / C is 0.314 A / mg Pt , which is about 6.1 times that of Pt / C and about 1.2 times that of the PtCo / C catalyst prepared in Comparative Example 2.
[0063] The chromium group element doped PtM alloy catalyst of the present invention reduces Pt and transition metal element M on a carbon carrier in steps by chemical reduction method, and the first reduced Pt provides an initial growth site for transition metal M, which is conducive to the uniform distribution and growth of the alloy under high temperature conditions; the PtM structure can effectively regulate the adsorption capacity of Pt nanoparticles to reaction intermediates, thereby regulating the catalyst activity. In addition, the doping of chromium group metal elements plays an electronic buffering role on the alloy catalyst, showing higher oxygen reduction activity and stability than PtM alloy, and is applied to the field of fuel cell catalysis.
Claims
1. A chromium group metal doped platinum alloy catalyst, characterized in that The catalyst is a PtM alloy nanoparticle doped with a chromium group element X uniformly supported on a carbon carrier; in the PtM alloy doped with the chromium group element X, X exists in a simple substance form, and the mass percentage of the chromium group element X is 5% to 10%; it is recorded as X-PtM / C, wherein X is Cr, Mo or W; and M is Fe, Co or Ni.
2. A method for preparing a chromium group metal-doped platinum alloy catalyst according to claim 1, characterized in that: The method proceeds as follows:
1. Preparation of Pt / C by polyol reduction method: Add the carbon carrier to a mixed solution of ethylene glycol and isopropanol, and disperse the carbon powder evenly by ultrasonic and magnetic stirring to obtain a carbon dispersion; then add an ethylene glycol solution of chloroplatinic acid to the carbon dispersion and stir evenly to obtain a slurry; then adjust the pH of the slurry to alkaline; Under the protection of inert gas, Pt is reduced to Pt nanoparticles by microwave heating; the pH of the slurry is adjusted to be acidic so that the Pt nanoparticles are loaded on the carbon carrier; the slurry is filtered, washed, vacuum dried, and ground evenly to obtain Pt / C particles; 2. Sodium borohydride reduction: Pt / C particles are dissolved in ultrapure water, and the Pt / C particles are evenly dispersed by ultrasonic and magnetic stirring, and a metal salt solution of a chromium group element X and a metal salt solution of M are added, and stirred evenly to obtain a mixed solution; sodium borohydride aqueous solution is added dropwise to the mixed solution under ice-water bath conditions, and stirring is continued for 2 to 3 hours after the addition is completed; then suction filtration, washing, vacuum drying, and grinding to obtain XM-Pt / C powder; 3. High temperature annealing: placing the XM-Pt / C powder in a high temperature furnace, heating it to 700-1100°C in a reducing atmosphere or an inert atmosphere and maintaining it for 0.5-4 hours for annealing, and grinding it evenly after cooling to obtain a primary product; during the high temperature annealing process, PtM alloy nanoparticles doped with chromium group element X are formed, and the particles are supported on the carbon carrier; 4. Acid washing treatment of heteroatoms on the catalyst surface: The initial product of step 1 is acid washed in a dilute sulfuric acid solution, then filtered and washed with ultrapure water until neutral, and vacuum dried to obtain a chromium group metal-doped platinum alloy catalyst, which is denoted as X-PtM / C.
3. The method for preparing a chromium group metal-doped platinum alloy catalyst according to claim 2, characterized in that: The carbon support described in step 1 is ECP-600JD, ECP-300JD or XC-72.
4. The method for preparing a chromium group metal-doped platinum alloy catalyst according to claim 2 or 3, characterized in that: The volume ratio of ethylene glycol to isopropanol in the mixed solution of ethylene glycol and isopropanol described in step 1 is (2-3):
1.
5. The method for preparing a chromium group metal-doped platinum alloy catalyst according to claim 2 or 3, characterized in that: The ratio of chloroplatinic acid to carbon carrier described in step 1 is (0.2-0.6):
1.
6. The method for preparing a chromium group metal-doped platinum alloy catalyst according to claim 2 or 3, characterized in that: The metal salt of the chromium group element X in step 2 is chromium chloride, chromium nitrate, molybdenum chloride, molybdenum nitrate, tungsten chloride or tungsten nitrate.
7. The method for preparing a chromium group metal-doped platinum alloy catalyst according to claim 2 or 3, characterized in that: The metal salt of M described in step 2 is nickel chloride, nickel nitrate, cobalt chloride, cobalt nitrate, ferric chloride or ferric nitrate.
8. The method for preparing a chromium group metal-doped platinum alloy catalyst according to claim 2 or 3, characterized in that: The ratio of the metal salt of the chromium group element X, the metal salt of M and the metal in the Pt / C particles described in step 2 is (0.1-0.3):(0.5-1):
1.
9. The method for preparing a chromium group metal-doped platinum alloy catalyst according to claim 2 or 3, characterized in that: The concentration of the dilute sulfuric acid solution described in step 4 is 0.05-0.1 M, and the pickling time is 2-6 hours.
10. The use of a chromium group metal-doped platinum alloy catalyst as claimed in claim 1, characterized in that The application is to use chromium group metal-doped platinum alloy catalysts in the cathode oxygen reduction reaction of fuel cells.
Citation Information
Patent Citations
Transition metal doped platinum-carbon catalyst as well as preparation method and application thereof
CN111129508A
Multi-element doped platinum-based catalyst and preparation method and application thereof
CN111224118A
Pt-based multi-component transition metal alloy nano electrocatalyst and preparation and application thereof
CN112825357A
Preparation method of Pt / C and PtM / C catalyst with high metal content
CN114243035A
Platinum alloy / carbon catalyst and preparation method and application thereof
CN116706108A
Cited By
Method for preparing platinum-based alloy catalyst by using plasma enhanced chemical vapor deposition low-temperature technology
CN120453394A
A method for preparing platinum-based alloy catalysts using plasma-enhanced chemical vapor deposition low-temperature technology
CN120453394B
Hydrogen fuel cell catalyst, preparation method and application thereof
CN121260823A
Gradient chromium-doped platinum-based ordered alloy catalysts, methods of making and using the same
CN122659164A